2020
DOI: 10.1161/strokeaha.120.030685
|View full text |Cite
|
Sign up to set email alerts
|

History of Stroke Is Independently Associated With In-Hospital Death in Patients With COVID-19

Abstract: Background and Purpose: In December 2019, an outbreak of severe acute respiratory syndrome coronavirus causing coronavirus disease 2019 (COVID-19) occurred in China, and evolved into a worldwide pandemic. It remains unclear whether the history of cerebrovascular disease is associated with in-hospital death in patients with COVID-19. Methods: We conducted a retrospective, multicenter cohort study at Mount Sinai Health System in New York City. Using our i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 8 publications
3
30
0
3
Order By: Relevance
“…In this cohort, the majority of patients with a prior cerebrovascular disease had a prior acute ischemic stroke (9.9%; 11/1,128), a prevalence which was higher than expected from U.S. 2013–2016 stroke estimates of 2.5% for adults ages > 20 years old ( 14 ). These results are consistent with published cohorts suggesting a greater number of hospitalized COVID-19 patients with cerebrovascular disease than prevalence estimates and increased likelihood of negative outcomes ( 4 , 8 , 10 13 , 16 , 17 , 21 , 28 31 ). The findings presented here extends our understanding of comorbidities that may contribute to increased risk of critical illness in COVID-19, and additionally suggests that critically ill COVID-19 patients with cerebrovascular disease may be prone to longer mechanical ventilation time than patients of similar ages and demographics without cerebrovascular disease.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In this cohort, the majority of patients with a prior cerebrovascular disease had a prior acute ischemic stroke (9.9%; 11/1,128), a prevalence which was higher than expected from U.S. 2013–2016 stroke estimates of 2.5% for adults ages > 20 years old ( 14 ). These results are consistent with published cohorts suggesting a greater number of hospitalized COVID-19 patients with cerebrovascular disease than prevalence estimates and increased likelihood of negative outcomes ( 4 , 8 , 10 13 , 16 , 17 , 21 , 28 31 ). The findings presented here extends our understanding of comorbidities that may contribute to increased risk of critical illness in COVID-19, and additionally suggests that critically ill COVID-19 patients with cerebrovascular disease may be prone to longer mechanical ventilation time than patients of similar ages and demographics without cerebrovascular disease.…”
Section: Discussionsupporting
confidence: 91%
“…Cerebrovascular comorbidities are common among older adults in the United States (U.S.) where an estimated 3% of adults have had a prior ischemic stroke (7.8 million) ( 20 ). A recent study from a U.S. cohort of 3,248 patients suggested an increased odds of in-hospital death among individuals with stroke and COVID-19, however, detailed data on other in-hospital adverse outcomes is largely unknown ( 21 ). Given that prior cerebrovascular disease is one of the most common neurological comorbidities in hospitalized patients with COVID-19, information regarding severe outcomes in this population would be valuable for prioritizing prevention strategies in the outpatient neurology setting, providing prognostic information for patients and families, and assisting hospital projections as countries experience increasing numbers of SARS-CoV-2 infections.…”
Section: Introductionmentioning
confidence: 99%
“…The association of WM microangiopathy, age and cardiovascular risk factors, with poor prognoses in patients with COVID-19 has been previously reported [22]: in the absence of a reliable medical history for these patients, microangiopathic changes can serve as a window to the patient's long-standing underlying risk factors and can provide potentially prognostic insights. With regard to COVID-19 patients, another recent study showed a higher mortality in those with a history of stroke [23].…”
Section: Discussionmentioning
confidence: 98%
“…Spätere Arbeiten konnten aber nachweisen, dass es sich um einen darüber hinaus gehenden schlaganfallspezifischen Effekt handelt. So demonstrierte beispielsweise eine für Komorbiditäten adjustierte Analyse einer großen Kohorte SARS-CoV-2-positiver Patienten/innen aus New York (n = 3248) eine unabhängige Risikoerhöhung für Mortalität während der COVID-19-bezogenen Hospitalisierung [10]. Überdies zeigte eine rezente vergleichende Kohortenstudie, dass COVID-19-Patienten/innen mit zerebralem Großgefäßverschluss nicht nur klinisch, sondern auch bildgebend eine erhöhte Schlaganfallschwere als SARS-CoV-2-negative Patienten/innen aufweisen, die sich in einem größeren Infarktkern und einem geringeren Diffusion-Weighted Imaging-Alberta Stroke Program Early CT Score darstellt [11].…”
Section: Klinische Evidenz Zur Durch Covid-19 Bedingten Risikoerhöhung Für Das Auftreten Eines Schlaganfallsunclassified